Effect of interactive visual education (EduVit) on anxiety in patients undergoing cardiac surgery - Sakulat, Obi Ferdinand; Wahyuni, Sri; Wuriningsih, Apriliani Yulianti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Anxiety is a common psychological issue experienced by patients undergoing cardiac surgery, which can significantly impact mental preparedness and the recovery process. Interactive Visual Education (EduVit) is a non-pharmacological intervention designed to reduce preoperative anxiety levels. Purpose: To determine the effect of interactive visual education (Eduvit) on reducing anxiety levels in patients undergoing cardiac surgery. Method: A one-group pretest–posttest approach within a quasi-experimental framework was adopted for this research. The sample consisted of 40 preoperative cardiac surgery patients at a central referral hospital in Central Java, selected using a total sampling technique. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (ZAS) both before and after the EduVit intervention. Results: Anxiety levels differed significantly across the two study phases (Marginal Homogeneity test, p < 0.001), demonstrating the effectiveness of the intervention. Conclusion: Interactive Visual Education is effective in reducing anxiety levels among preoperative cardiac surgery patients and is recommended as a standard nursing intervention. Keywords: Anxiety; Cardiac Surgery; Interactive Visual Education; Preoperative Care.